Laboratory and field studies to evaluate the potential of an open rearing system of Lysiphlebus testaceipes for the control of Aphis craccivora in Argentina - Zumoffen, Leticia; Tavella, Julia Rita; Signorini, Marcelo; Salvo, Silvia Adriana (2018)
The aim of this work was to examine, both in the field and in the laboratory, ecological aspects of selected plant–aphid–parasitoid interactions to evaluate their potential for the open rearing of the parasitoid Lysiphlebus testaceipes (Cresson) (Hymenoptera: Aphidiinae) for the control of Aphis craccivora (Koch) (Hemiptera: Aphididae) in alfalfa agroecosystems. To this end quantitative samplings of parasitoids and aphids were made fortnightly in three alfalfa crop fields and their spontaneously vegetated edges, in Rafaela (Santa Fe, Argentina), during three years (2009–2011). Three sink webs based on L. testaceipes, on a per-year basis, were constructed to assess the strength of the interactions established by aphids and parasitoids, the host ranges of alternative aphid species, and the tendencies in parasitoid host use across years. In the laboratory, emergence rates, parasitism rates, larval and pupal development times, and adult lifespan of L. testaceipes were analyzed by means of choice tests, including the alternative and the target aphid species in the assays. About 84 % of adults of L. testaceipes obtained in the samples came from Aphis nerii (Boyer de Fonscolombe), an innocuous aphid species only associated with plants of the genus Araujia Brotero (Apocynaceae). Based on our results, the system proposed has many features that support its feasibility to be used as an open rearing system of L. testaceipes: unrisky alternative aphid, easy reproduction of the banker plant and similar suitability of innocuous and pest aphid species for the parasitoid to oviposit and complete their development without noticeably preference for specific hosts.